(untitled) (Nexo Revista Científica, 2020)
The study area is located in northern Iran and is part of the Alborz mountain range. The exposed rock units in the study area are mostly Eocene volcanic rocks with some Oligomiocene intrusive masses included and locally Paleocene, Jurassic, Permian and Carboniferous sedimentary outcrops. The intrusive rocks of the study area are mostly gabbro and olivine gabbro in terms of mineralogical composition, but intermediate types such as porphyry monzonite are also rarely seen. Based on the results of microprobe analysis, pyroxenes have augite and diopside compositions, orthopyroxenes are hypersthenes, biotites have magnesium biotite and phlogopite compositions, olivines have hyalosiderite compositions and amphiboles are pargasite and ferropargasite compositionally. The results of temperature and pressure evaluation indicate a temperature range of 650 to 1200 ° C and pressure range >2-5 KB. Based on the chemistry of clinopyroxene mineral of the mentioned intrusions, magma that made these intrusions is of the sub-alkaline type and is formed in a volcanic arc tectonic setting.